(untitled) (Research, Society and Development, 2021)
The water may be contaminated in the capture of the aquatic resources or during the treatment, distribution and reservation. For this reason, the objective of this study was to characterize the supply, monitoring and quality of water for human consumption in the municipality of Rosário-MA, so that there is support for new decision-making and changes to improve environmental quality and population health, and also aimed to propose an alternative water treatment. For this, data were collected on the supply, quality and monitoring of municipal water, through four stages: characterization of the water supply system, analysis of the procedures adopted, survey of the quality of the water in the wells and of the water distributed to population and intervention to improve the supply system. Thus, the presence of total coliforms was found between 11% to 32% of the collected samples and the presence of E. coli from 3% to 9% of the well samples, varying between the years 2007 and 2017. In the distribution network, most of the samples were in non-compliance with the legislation, with total coliforms between 52.9% to 100% of the samples and E. coli from 13.33% to 68.48% of the samples. The monitoring and quality of drinking water in the municipality of Rosário-MA, are not in accordance with the legislation, thus requiring the implementation of corrective measures proposed in this work.